Effect of starvation and exercise on actual and total activity of the branched-chain 2-oxo acid dehydrogenase complex in rat tissues. - Wagenmakers, A J (1984)
Starvation does not change the actual activity per g of tissue of the branched-chain 2-oxo acid dehydrogenase in skeletal muscles, but affects the total activity to a different extent, depending on the muscle type. The activity state (proportion of the enzyme present in the active state) does not change in diaphragm and decreases in quadriceps muscle. Liver and kidney show an increase of both activities, without a change of the activity state. In heart and brain no changes were observed. Related to organ wet weights, the actual activity present in the whole-body muscle mass decreases on starvation, whereas the activities present in liver and kidney do not change, or increase slightly. Exercise (treadmill-running) of untrained rats for 15 and 60 min causes a small increase of the actual activity and the activity state of the branched-chain 2-oxo acid dehydrogenase complex in heart and skeletal muscle. Exercise for 1 h, furthermore, increased the actual and the total activity in liver and kidney, without a change of the activity state. In brain no changes were observed. The actual activity per g of tissue in skeletal muscle was less than 2% of that in liver and kidney, both before and after exercise and starvation. Our data indicate that the degradation of branched-chain 2-oxo acids predominantly occurs in liver and to a smaller extent in kidney and skeletal muscle in fed, starved and exercised rats.